Degradation of ionic liquids by a UV/H2O2 process and CMCase from novel ionic liquid-tolerant alkaliphilic Nocardiopsis sp. SSC4. Issue 4 (4th July 2017) - Kurata, Atsushi; Shimizu, Shota; Shiraishi, Yutaro; Abe, Mihoko; Naito, Nobutoshi; Shimada, Mihoko; Kishimoto, Noriaki
ABSTRACT: We demonstrated the degradation of two ionic liquids (1-butyl-3-methylimidazolium chloride, [BMIM]Cl, and 1-ethylpyridinium bromide, [EtPy]Br) that are useful for the solubilization of wood components. [BMIM] + and [EtPy] + were detected by thin-layer chromatography (TLC) and electrospray ionization–mass spectrometry (ESI-MS). [BMIM] + was harder to degrade than [EtPy] + . Ultraviolet (UV) irradiation with 0.2% ( v / v ) H2 O2 for 16 h degraded 1 mmol/L [BMIM] +, whereas UV irradiation alone degraded 1 mmol/L [EtPy] + . Additionally, we isolated an ionic liquid-tolerant alkaliphilic actinomycete, Nocardiopsis sp. SSC4. Strain SSC4 produced carboxymethylcellulase (CMCase) in the presence of 1.0% ( v / v, 48.1 mmol/L) 1-ethyl-3-methylimidazolium trifluoromethanesulphonate ([EMIM]CF3 SO3 ), which is useful for the extraction of cellulose-rich materials from wood. In the case of strain SSC4, CMCase was inducibly synthesized by more than 0.5% CMC. The addition of 0%–1.0% tryptone or 0%–2.0% yeast extract decreased the CMCase activity in a concentration-dependent manner. After cultivation of strain SSC4 with 1.0% ( w / v ) CMC medium (pH 9.0) for 48 h at 37 °C, the culture supernatant exhibited CMCase activity at 0.03 U/mg. The optimum reaction temperature of CMCase was 45 °C. CMCase was stable up to 37 °C for 20 h incubation. The degradation characteristics of [BMIM] + and [EtPy] + and the activity of CMCase in the presence of [EMIM]CF3 SO3 may be useful for the development of a bioconversion system for biomass resources.